Mechanism of metamorphic fluid expulsion from ductile contact aureole: Insights from numerical modeling of a growing mid-crustal magma chamber - Chen, Yanying; Li, Zhong-Hai; Tang, Kun; Shi, Yaolin (Earth and planetary science letters, 2024)
•Metamorphic fluid flow in the ductile aureole above a growing laccolith is modeled.•Fluid moves as a porosity wave and can be expelled from the compacting aureole.•Continuous pluton growth leads to elevated fluid pressure and dilational deformation.•Episodic pluton growth results in top dilational process but basal pore compaction.•Hydraulic fractures can form during low-frequency, high-flux pluton growth. Metamorphic fluid flow around an igneous intrusion is governed by temperature, rheology, permeability and fluid pressure condition in the contact aureole. In the middle crust, where lithostatic fluid pressure and ductile deformation dominate, the impulse from incremental magma chamber growth facilitates ductile aureole compaction and induces syn-intrusive metamorphic devolatilization. However, the mechanism of metamorphic fluid expulsion from ductile contact aureole is vaguely understood. In this study, we numerically modeled the two-phase solid-fluid flow process in the ductile aureole above the growing chamber to examine the potential for fluid expulsion, the pattern of fluid flow and fluid pressure condition. The numerical model is constructed based on the geological structure of the Papoose Flat pluton in California, applying three different modes of pluton growth: continuous growth, episodic growth with an interval of 100 years and episodic growth with an interval of 1000 years. The results indicate that the metamorphic fluids propagate in the form of porosity wave in the ductile aureole with solid matrix compaction. Continuous pluton growth, with a slow pressurization of aureole, leads to a positive fluid pressure anomaly in most of the aureole, whereas the episodic growth results in a negative fluid pressure anomaly at the base and positive fluid pressure anomaly at the top of the aureole. Hydrofracturing can occur in the inner aureole, and the outer aureole may retain some fluid with low-frequency, high-flux magma injections. The solid-fluid flow models indicate that porosity wave is an important mechanism for metamorphic fluid expulsion from the pluton and wall rock system.